2021
DOI: 10.3390/jmse9111216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clay Mineral Composition on the Dynamic Properties and Fabric of Artificial Marine Clay

Abstract: Marine clays are easily affected by different mineral composition in cyclic load-based geological hazards. Therefore, based on analyzing the mineral composition of natural marine clay, it is the key to predict the dynamic properties of natural materials under cyclic loading by using quantitated artificial marine clay. In this study, the marine clay found in the South China Sea deltas was investigated. Based on the results of geological conditions and mineral composition analyses, raw non-clay minerals (such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…These parameters should be material properties that vary with the composition of each soil sample. The jamming fraction was determined from the high-γ regime where viscosity is independent of γ, and where we expect the influence of cohesion and aggregation to be negligible (44,45). The data verify that there is no relation between ϕ m and sample mineralogy (Fig.…”
Section: Materials Controls On Flow Parametersmentioning
confidence: 59%
“…These parameters should be material properties that vary with the composition of each soil sample. The jamming fraction was determined from the high-γ regime where viscosity is independent of γ, and where we expect the influence of cohesion and aggregation to be negligible (44,45). The data verify that there is no relation between ϕ m and sample mineralogy (Fig.…”
Section: Materials Controls On Flow Parametersmentioning
confidence: 59%
“…These parameters are critical to the design and stability of marine engineering and subsea infrastructure. Shan et al [56] conducted dynamic triaxial laboratory tests on manmade marine clays containing various clay minerals under the same test conditions and confirmed that clay minerals, especially montmorillonite, significantly affect the dynamic properties of large strains.…”
Section: Marine Claymentioning
confidence: 90%
“…However, in these areas, there are large areas of soft soil which has the characteristics of large porosity ratio, high water content, high compressibility, and low strength. When the highways are constructed on soft soil, the subgrade's large settlement or uneven settlement will occur [1,2]. This is very harmful to subgrade stability.…”
Section: Introductionmentioning
confidence: 99%